Evaluation of modis-aqua and olci chlorophyll-a products in contrasting waters of the southwestern Atlantic ocean - Delgado, Ana Laura (2020)
Satellite chlorophyll-a concentration (Chl-a) estimations provide a valuable tool to study marine phytoplankton dynamics with unprecedented spatial and temporal coverage. Standard empirical Chl-a algorithms perform well where phytoplankton is the dominant optically active component in seawater, but usually fail in those regions where there is a high optical influence from multiple dissolved and particulate components that are not covariant with Chl-a (Prieur and Sathyendrenath, 1981). Therefore, in coastal regions, where colored dissolved and suspended particulate matter are dominant, it is crucial to perform an accuracy assessment of satellite Chl-a products to ensure their reliable use.